2008
DOI: 10.1590/s0102-36162008000400005
|View full text |Cite
|
Sign up to set email alerts
|

Análise comparativa em modelo computadorizado bidimensional com simulação do emprego de hastes flexíveis de aço e titânio, na fratura do fêmur da criança, utilizando o método dos elementos finitos

Abstract: Análise comparativa em modelo computadorizado bidimensional com simulação do emprego de hastes flexíveis de aço e titânio, na fratura do fêmur da criança, utilizando o método dos elementos finitos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
1
9
0
7
Order By: Relevance
“…Since then, several other studies have been conducted 6 , 7 , 8 , 9 , 10 , 11 . Studies using this technique have also been published in the Brazilian literature, but not with simulation of an external fixator 12 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other studies have been conducted 6 , 7 , 8 , 9 , 10 , 11 . Studies using this technique have also been published in the Brazilian literature, but not with simulation of an external fixator 12 , 13 , 14 .…”
Section: Discussionmentioning
confidence: 99%
“…Since then, several other studies have been conducted (6)(7)(8)(9)(10)(11) . Studies using this technique have also been published in the Brazilian literature, but not with simulation of an external fixator (12)(13)(14) . The commercial finite-element packages available are very versatile tools for evaluating the influence of A B C assembly parameters in relation to the axial stiffness of a particular external fixator, because of the ease of modifying the geometrical characteristics of the assembly and outline conditions of the model.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, Soni et al . (4) presented a two-dimensional computer model, simulating a fracture of the femur in children treated with flexible steel and titanium nails, comparatively assessing the stress distribution. They concluded that the biomechanical behavior was qualitatively better in the model with titanium nails.…”
Section: Steel or Titanium Nails?mentioning
confidence: 99%
“…Nonunion or delayed union are uncommon and when they occur, it seems to be related to the inappropriate use of surgical techniques. Complications are limited to the skin or discomfort at the site of nail insertion 1 , 2 , 3 , 4 , 5 . Changes in bone length due to growth disturbances appear to be minimal, with an average of overgrowth of the femur of about 1.2 mm (12) .…”
Section: Steel or Titanium Nails?mentioning
confidence: 99%